2016
DOI: 10.4103/0019-5413.193487
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of intraarticular distal humerus fracture fixation using triceps-sparing paratricipital approach

Abstract: Background:Displaced intraarticular distal humerus fracture has been conventionally treated operatively with various triceps disrupting approaches. These approaches are associated with several complications, such as triceps weakness, nonunion or delayed union of osteotomy, implant prominence, and delayed mobilization of the elbow. We present the functional outcome of intraarticular distal humerus fracture fixation using a triceps-sparing paratricipital approach which allows early elbow mobilization and preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…All surgeries were performed in the supine position under general anesthesia using a tourniquet. Each approach was performed using standard methods [ 14 , 15 , 16 , 17 ]. In the posterior approach, the ulnar nerve was first identified and protected.…”
Section: Methodsmentioning
confidence: 99%
“…All surgeries were performed in the supine position under general anesthesia using a tourniquet. Each approach was performed using standard methods [ 14 , 15 , 16 , 17 ]. In the posterior approach, the ulnar nerve was first identified and protected.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted for supracondylar humerus fracture in adults treated by open reduction and internal fixation by parallel plates by olecranon osteotomy technique and they were followed up clinically and radiologically for 6 months. Yadav et al (19) reported that, the olecranon osteotomy approach does not seem to have a clinical advantage over the approaches that preserve the integrity of the elbow extensor device. However, a systematic review and meta-analysis conducted by Chen et al (20) compared various surgical approaches on elbow functional outcomes for patients with distal humerus intercondylar fractures (DHF).…”
Section: Discussionmentioning
confidence: 99%
“…The patient was put in a prone position on the examination table with the arm in 90° abduction, the elbow in 90° flexion, and the forearm in neutral rotation. With one hand of the surgeon supporting the patient's arm just above the elbow and the other hand applying resistance on the dorsal surface of the patient's forearm, the patient was asked to extend the elbow against resistance 16 …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the surgical approach that preserves the integrity of the elbow extensor device has been developed. Some scholars believe that a paratricipital approach was sufficient to meet the requirements of the surgical field without an olecranon osteotomy for type C distal humerus fractures 16,17 . The paratricipital approach was particularly suitable for extra‐articular and intra‐articular distal humerus fractures which were not complicated (C1 and C2 fractures) since it could preserve triceps continuity and the attachment to olecranon.…”
Section: Introductionmentioning
confidence: 99%